Repigmentation and curling of hair after acitretin therapy - SEÇKİN GENÇOSMANOĞLU, DİLEK (WILEY, 2009)
Drug-induced hair colour and texture changes have been reported rarely. We describe a 70-year-old woman with psoriasis who noticed darkening of her previously white hair, which also gained a curly appearance after 6 months of acitretin treatment. We present this case to emphasize that acitretin can be added to the list of drugs that induce changes in hair colour and texture.
Keywords: acitretin; curling; hair repigmentation; WHITE HAIR